2012
DOI: 10.1590/s2176-94512012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ortho Primer Morelli adhesion booster on orthodontic brackets shear bond strength

Abstract: OBJECTIVE: This work aimed at assessing the bond strength (AS), the site of the flaw and the relation between them and Ortho Primer Morelli® (OPM) adhesion optimizer. METHODS: Sixty test specimens, made out of bovine permanent lower incisors, were divided into three groups: TXT Primer (control), in which a conventional adhesive system was applied (primer and paste); OPM, in which TXT primer was replaced by OPM; and TXT without Primer, in which only TXT paste was used. A shear force was applied at a speed of 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Hence, the achievement of desirable shear strength does not depend on the requirement of adhesive resin wettability. This consideration may be valid for both as flowable, 24 orthodontic, 17 or restorative resins, since no significant differences in bond strength were found among them (P 5 .42), and this adhesive variable did not interfere with the ones included on the multivariate test. According to Shahabi et al, 21 another suggestion of adhesive resin application to protect enamel against debonding force 25 is not unanimous, owing to their findings that the application had no effect on the quality or quantity of cracks whether it was applied in one or two layers.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hence, the achievement of desirable shear strength does not depend on the requirement of adhesive resin wettability. This consideration may be valid for both as flowable, 24 orthodontic, 17 or restorative resins, since no significant differences in bond strength were found among them (P 5 .42), and this adhesive variable did not interfere with the ones included on the multivariate test. According to Shahabi et al, 21 another suggestion of adhesive resin application to protect enamel against debonding force 25 is not unanimous, owing to their findings that the application had no effect on the quality or quantity of cracks whether it was applied in one or two layers.…”
Section: Discussionmentioning
confidence: 94%
“…After bias risk analysis (Table 1), one study 11 was excluded due to its high risk of bias. Nine studies 2,3,8,[12][13][14][15][16][17] were included; descriptive data, random-effect means, confidence interval, and weight of each study are shown in Table 2. The lowest mean for bond strength in a group was 6.42 MPa; the highest value was 34.8 MPa, with 50% of the groups' means being lower than 11.0 MPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation